Breakthrough Pain in Patients with Controlled or Uncontrolled Pain: An Observational Study - Antonio Gatti; Marta Gentili; Marco Baciarello; Marzia Lazzari; Rossella Marzi; Elisa Palombo; Alessandro F Sabato; Guido Fanelli (Pain Research and Management)
BACKGROUND: Breakthrough pain (BTP) is traditionally defined as a pain exacerbation in patients with chronic controlled pain. However, this definition has recently been challenged.